HAMBATAN DAN TANTANGAN PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI - Erwin Sawitri; Made Sumiati Astiti; Yessi Fitriani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Along with the development of Information and Communication Technology (ICT) that is increasingly rapid, the need for a concept and mechanism for ICT-based teaching and learning (educators) becomes inevitable. The concept which was later known as e-learning brought the influence of the process of converting conventional education into digital form, both in terms of contents and systems. E-learning as a new learning model in education provides a great role and function for the world of education which has been charged with the many shortcomings and weaknesses of education, including limited space and time in the education process. E-learning is a term used for learning that utilizes communication and information technology in various ways to support and improve the learning process. There are various kinds of technologies that can be used, ranging from online and offline computer applications, presentation technologies such as Microsoft PowerPoint applications or projectors, World Wide Web, web conferences, multimedia materials such as photos or animations, tools to assess student work, games, and still much more. In implementing ICT-based learning, there are many challenges and obstacles. One of the challenges and obstacles in the application of ICT-based learning is that the inequality of infrastructure that supports the application of ICT in the education sector is an initial problem that must be resolved by the authorities, because without the infrastructure that supports the implementation of ICT in education mere dreams.